Temporal Microbial Community Dynamics in Microbial Electrolysis Cells – Influence of Acetate and Propionate Concentration - Hari, Ananda Rao; Venkidusamy, Krishnaveni; Katuri, Krishna P.; Bagchi, Samik; Saikaly, Pascal E. (Frontiers in Microbiology, 2017)
Microbial electrolysis cells (MECs) are widely considered as a next generation wastewater treatment system. However, fundamental insight on the temporal dynamics of microbial communities associated with MEC performance under different organic types with varied loading concentrations is still unknown, nevertheless this knowledge is essential for optimizing this technology for real-scale applications. Here, the temporal dynamics of anodic microbial communities associated with MEC performance was examined at low (0.5 g COD/L) and high (4 g COD/L) concentrations of acetate or propionate, which are important intermediates of fermentation of municipal wastewaters and sludge. The results showed that acetate-fed reactors exhibited higher performance in terms of maximum current density (I: 4.25±0.23A/m2), coulombic efficiency (CE: 95±8%) and substrate degradation rate (98.8±1.2%) than propionate-fed reactors (I: 2.7±0.28 A/m2; CE: 68±9.5%; substrate degradation rate: 84±13%) irrespective of the concentrations tested. Despite of the repeated sampling of the anodic biofilm over time, the high-concentration reactors demonstrated lower and stable performance in terms of current density (I: 1.1±0.14 to 4.2±0.21 A/m2), coulombic efficiency (CE: 44±4.1 to 103±7.2%) and substrate degradation rate (64.9±6.3 to 99.7±0.5%), while the low-concentration reactors produced higher and dynamic performance (I: 1.1±0.12 to 4.6±0.1 A/m2; CE: 52±2.5 to 105±2.7%; substrate degradation rate: 87.2±0.2 to 99.9±0.06%) with the different substrates tested. Correlating reactor’s performance with temporal dynamics of microbial communities showed that relatively similar anodic microbial community composition but with varying relative abundances was observed in all the reactors despite differences in the substrate and concentrations tested. Particularly, Geobacter was the predominant bacteria on the anode biofilm of all MECs over time suggesting its possible role in maintaining functional stability of MECs fed with low and high concentrations of acetate and propionate. Taken together, these results provide new insights on the microbial community dynamics and its correlation to performance in MECs fed with different concentrations of acetate and propionate, which are important volatile fatty acids in wastewater.